Humanitarian Protection Advocacy in East Asia: Charting a Path Forward. (19th January 2018) - Wolman, Andrew
ABSTRACT: In this article, I make the following three-part argument. Firstly, I claim that despite the fact that a far greater number of asylum-seekers in Japan, Korea, and Mainland China receive humanitarian protection status than receive refugee status, legal advocacy regarding asylum in East Asia disproportionately focuses on refugee law and policy. Secondly, I argue that by neglecting a potentially productive advocacy framework, this disproportionate focus on refugee law has deleterious consequences for the development of robust and humane asylum systems in the region and for the provision of asylum protection to the greatest number of individuals. Thirdly, I assert that international law provides tools for effective humanitarian protection-based advocacy, and outline four avenues for legal advocacy that I believe can lay the groundwork for progressive reforms of humanitarian protection law and policy in East Asia.